64 Effect of grass silage chop length when fed alone, or with corn silage, on digestion and metabolism in dairy cows. (7th December 2018) - Tayyab, U; Wilkinson, R; Reynolds, C; Sinclair, L
Abstract: Our aim was to evaluate the effects of ryegrass silage (GS) chop length (CL) and ratio of GS to corn silage (CS) in the diet on digestibility and blood metabolites of dairy cows. Ryegrass was chopped at 2 mean CL (short; 31 and long; 44 mm) and mixed with CS (GS:CS) at 100:0 or 40:60 ratio (dry matter [DM] basis) of the forage fed at 54% of DM in isonitrogenous diets. Sixteen lactating multiparous Holstein-Friesian cows were used in a 4 × 4 Latin Square design with 4 periods of 28-d duration. Total-tract digestibility was estimated using acid-insoluble-ash (AIA) as an internal marker, and fecal samples were analysed for DM, nitrogen (N), ash, AIA, neutral detergent fiber (NDF) and acid detergent fibre (ADF). Blood samples were collected over 2-d during the final week at 0900, 1100, 1230 and 1400h. Data were analysed as a Latin square design in 2 × 2 factorial arrangement using GenStat®18.1. There was an interaction (P < 0.05) for DM, organic matter, N and ADF digestibility, where short CL increased digestibility for 100:0 GS:CS, but had no effect for 40:60 GS:CS. Digestibility of NDF was 0.228 kg/kg higher (P < 0.01) for 100:0 GS:CS compared to 40:60 GS:CS. Plasma glucose concentration decreased (P < 0.01) after feeding and was 0.17 mmol/l higher (P < 0.01) when cows were fed 40:60 GS:CS than 100:0 GS:CS. Plasma β-hydroxybutyrate concentration increased (P < 0.01) post feeding, but was not affected (P > 0.05) by treatment. Cows fed 40:60 GS:CS had 0.86 mmol/l higher (P < 0.01) plasma urea concentration compared to 100:0 GS:CS. In conclusion, shorter GS CL increased diet component digestibility when GS was the sole forage, but had little effect when fed with CS. Chop length had no effect on blood metabolites but feeding CS increased plasma glucose and urea concentration.